PENERJEMAHAN LABEL PRODUK MAKANAN, OBAT-OBATAN DAN KOSMETIK - Maulani Pangestu (Wanastra: Jurnal Bahasa dan Sastra, 2014)
The purpose of this study is to investigate and to find a crystal clear picture of label products translation especially in foods, drugs and cosmetics. This study is a qualitative study using content analysis techniques. The objects of study are foods, drugs and cosmetics product labels which have Source Language in bahasa Indonesia and translated into English. All products are produced by Indonesia companies and have bilingual product labels. The data of the study which are foods, drugs and cosmetics label products were analyzed with translation theory. Viewed from the aspect of translation equivalence, the formal equivalence dominates than dynamic equivalence. The benefits of this research could be used as additional information and reference for anyone who wants to study translation especially translation of label products foods, drugs and cosmetics.